(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem of pedagogical conditions for putting o practice interactive methods of teaching in primary-school classes. The ways of improving the lesson, which are in the close interrelation with the organizational forms of younger schoolchildren learning activities in modern didactics are shown.